Examining self-employment policies for persons with disabilities in South Africa: Perspectives from policy actors - Luther Lebogang Monareng; Shaheed Mogammad Soeker; Deshini Naidoo (PLoS ONE, 2025)
Background Despite robust global and national efforts to promote inclusive development, a significant gap persists in countries such as South Africa’s self-employment policies for persons with disabilities. The existing legislative framework, although well-intentioned, lacks clear and comprehensive guidance on self-employment as a viable placement option for persons with disabilities. Consequently, this ambiguity hinders effective policy implementation, limiting economic empowerment and social inclusion. This research aimed to explore the existence of self-employment-specific policies for persons with disabilities and policy actors’ involved in South Africa. Methods The participants (n = 47) had an average of 10 years of experience in self-employment for persons with disabilities, holding qualifications ranging from no formal education to master’s degrees. This qualitative study ensured transparent and systematic reporting using the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Purposive and snowball sampling were utilised to recruit participants. Data were collected using a piloted question guide and analysed using the NVIVO software. Data was analysed thematically. Ethics clearance, relevant gatekeepers’ permission and informed written consent from participants were obtained. Results Two themes emerged, namely, theme one: The status quo on self-employment-specific policies for persons with disabilities. Participants reported on the absence of explicit policies on self-employment for persons with disabilities, the lack of effectiveness in inclusive South African legal frameworks and their lack of impact on promoting self-employment opportunities. Theme two: policy actors’ involvement in self-employment-specific policies for persons with disabilities. Participants reported on the roles and responsibilities of policy actors and strategies to promote self-employment opportunities for persons with disabilities through policy reforms. Conclusions The research revealed a complex policy landscape where the absence of self-employment-specific policies for persons with disabilities coexists with potentially leverageable inclusive frameworks. These coexist with potential policy actors who have the potential to facilitate implementation. Leveraging existing policies through effective implementation and targeted policy reforms would ensure the full participation of persons with disabilities in self-employment. Key policy actors should familiarise themselves with the existing legal framework and emphasise enforcement and consequence management to ensure policies are implemented effectively. Furthermore, a coordinated approach is necessary, involving: a single or integrated system or database to streamline policy implementation and monitoring; a targeted approach that prioritises persons with disabilities in self-employment; and policies that allow for target setting, accurate measurement of targets, and effective monitoring and evaluation. Thus, a policy brief outlining the key findings should be considered, drafted, and submitted to the relevant government department (e.g., Department of Employment and Labour) for further action.